The PRIMA Test Facility: SPIDER and MITICA test-beds for ITER neutral beam injectors. (24th August 2017) - Toigo, V; Piovan, R; Bello, S Dal; Gaio, E; Luchetta, A; Pasqualotto, R; Zaccaria, P; Bigi, M; Chitarin, G; Marcuzzi, D; Pomaro, N; Serianni, G; et al.
Abstract: The ITER Neutral Beam Test Facility (NBTF), called PRIMA (Padova Research on ITER Megavolt Accelerator), is hosted in Padova, Italy and includes two experiments: MITICA, the full-scale prototype of the ITER heating neutral beam injector, and SPIDER, the full-size radio frequency negative-ions source. The NBTF realization and the exploitation of SPIDER and MITICA have been recognized as necessary to make the future operation of the ITER heating neutral beam injectors efficient and reliable, fundamental to the achievement of thermonuclear-relevant plasma parameters in ITER. This paper reports on design and R&D carried out to construct PRIMA, SPIDER and MITICA, and highlights the huge progress made in just a few years, from the signature of the agreement for the NBTF realization in 2011, up to now—when the buildings and relevant infrastructures have been completed, SPIDER is entering the integrated commissioning phase and the procurements of several MITICA components are at a well advanced stage.